Caracterização e uso de formulação de biofertilizante à base de Aspergillus niger - Silva, Patrick Vieira (2022)
Aspergillus niger has the potential to solubilize insoluble inorganic phosphate compounds and to promote plant growth. Therefore, this work aimed to characterize a granular formulation based on A. niger in terms of its shelf life, evaluate its compatibility with fertilizers and determine its potential in promoting the growth of lettuce and bean plants. The results indicate that the formulation can be stored at room temperature or in the refrigerator for at least 6 months. The biofertilizer is compatible for fungal growth with urea, potassium chloride, single superphosphate, triple superphosphate and organomineral. For compatibility in liquid medium, urea inhibited phosphate solubilization. Other fertilizers were compatible, while potassium chloride and organomineral contributed to a higher percentage of solubilization. Seed inoculation with A. niger can be used at different doses of P to promote lettuce growth. At the 100% dose, the different inoculation methods contributed to higher values in the parameters of plant diameter, SPAD index, fresh weight and number of leaves. In common bean, the microorganism A. niger contributes to plant development, promoting greater number of leaves, height, number of nodules, dry weight of shoots and roots. The WG formulation used in the seed treatment was superior to the granular formulation. Aspergillus niger is compatible with the inoculant for biological nitrogen fixation, in addition to contributing to the increase in the number of nodules per plant. The source and dose of phosphate fertilizer that ensured greater increases in the parameters evaluated was triple superphosphate with 100% of the plant's need. The biofertilizer containing the fungus A. niger has potential for storage during the period of 6 months without losing its characteristics, compatibility with fertilizers and growth promotion of lettuce and beans plants.